(untitled) (Annals of Medical Research, 2021)
Aim: Comparison of optic nerve with healthy subjects by MRI histogram analysis in patients with multiple sclerosis (MS). Material and Methods: A total of 78 patients with age range of 39 ms (18-54), 27 females, 12 males and 39 healthy age range (19-54), 26 females and 13 males (control group) were included in the study. The right optic nerve in the MS and control group was included in the study. ROI was placed on the optic nerve from the images and numerical data were obtained by histogram analysis. Numerical data were loaded into MATLAB program.Results: Mean, standard deviation, minimum, maximum, median, variance and entropy values were significantly higher in MS patients than control group(p0.05). In MS patients, changes in tissue histology were detected in the optic nerve compared to healthy individuals by mri histogram analysis without a visual change in the optic nerve.Conclusion: We think that the diagnosis of optic neuritis, which has an important role in disability in MS patients, will improve the quality of life of patients with early diagnosis and treatment by MRI histogram analysis of the optic nerve.